The Influence of the Work Environment on Employee Job Satisfaction at the Wera Subdistrict Office, Bima Regency - Kuriman, Kuriman; Jaenab, Jaenab; Hidayanti, Mawar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to determine the influence of the work environment on employee job satisfaction at the Wera sub-district office, Bima Regency. This research is included in the Associative research category. The population in this study used all employees at the Bima Regency Wera sub-district office, totaling 73 employees. The research technique used was purposive sampling. The research sample used was all 38 employees with State Civil Apparatus (ASN) status. The instrument in this research is a questionnaire with a Likert scale. Observation data collection techniques, questionnaires, literature study. Data analysis techniques use validity tests, reliability tests and simple linear regression tests, then processed using SPSS. The results of the research show that the work environment has a significant effect on employee job satisfaction at the Wera sub-district office, Bima Regency.